Rapid detection of resistance to pyrazinamide in Mycobacterium tuberculosis using the resazurin microtitre assay - Zanetti Campanerut, Paula Aline; Ghiraldi, Luciana Dias; Espinoza Spositto, Fernanda Luisa; Sato, Daisy Nakamura; Leite, Clarice Queico Fujimura [UNESP]; Hirata, Mario Hiroyuki; Crespo Hirata, Rosario Dominguez; Cardoso, Rosilene Fressatti (Oxford University Press, 2011)
Objectives: The resazurin microtitre plate assay (REMA) was evaluated to determine the susceptibility of Mycobacterium tuberculosis to pyrazinamide, and was compared with the broth microdilution method (BMM), the absolute concentration method (ACM) and pyrazinamidase (PZase) determination.Methods: Thirty-four M. tuberculosis clinical isolates (26 susceptible and 8 resistant to pyrazinamide) and reference strains M. tuberculosis H37Rv ATCC 27294 and Mycobacterium bovis AN5 were tested.Results: REMA and BMM showed 100% specificity and sensitivity when compared with ACM; BMM, however, demanded more reading time. The PZase determination assay showed 87.50% and 100% sensitivity and specificity, respectively.Conclusions: All tested methods in this preliminary study showed excellent sensitivity and specificity for the determination of pyrazinamide susceptibility of M. tuberculosis, but REMA was faster, low-cost and easy to perform and interpret. Additional studies evaluating REMA for differentiating pyrazinamide-resistant and-susceptible M. tuberculosis should be conducted on an extended panel of clinical isolates.
Keywords: TB; mycobacteria; susceptibility testing